Patterns of Depression Among Adolescent Mothers: Resilience Related to Father Support and Home Visiting Program. - Easterbrooks, M. Ann.; Kotake, Chie.; Raskin, Maryna.; Bumgarner, Erin. (Tufts University. Tisch Library., 2017)
The negative consequences of maternal depression are a major public health concern, both for mothers and for their children. Despite the high prevalence of depression among adolescent mothers, little is known about the patterns of adolescent mothers' depression in the early parenting years. The present study examined mothers' depression during the first 2 years following childbirth in a sample of 428 young mothers (20 or younger at first childbirth) who were participants in a randomized controlled trial of a home visiting parenting support program. Depressive symptoms were assessed using the self-reported Center for Epidemiological Studies Depression Scale (CES-D) Mothers were classified into groups based on whether their depressive symptoms were below or above the cutoff for clinically significant symptomatology. Depression groups (stable nondepressed, stable depressed, remitted depression) were associated with variations in mothers' satisfaction with support from the baby's father and enrollment in the home visiting program. Maternal depression was more likely to remit when mothers were satisfied with father support; assignment to the home visiting program was associated with mothers remaining mentally healthy. Results have clinical and policy implications for prevention and intervention programs. ©American Psychological Association, 2016. This paper is not the copy of record and may not exactly replicate the authoritative document published in the APA journal. Please do not copy or cite without author's permission. The final article is available, upon publication, at: http://dx.doi.org/10.1037/ort0000093.